Clinical Outcome in Croatian War Veterans with Chronic Pain and Chronic Posttraumatic Stress Disorder - Braš, Marijana; Lončar, Zoran; Brajković, Lovorka; Gregurek, Rudolf; Erceg, Inja (2008)
Aim of Investigation: Chronic pain in the musculoskeletal system is one of the most frequent physical complaints in patients with chronic post-traumatic stress disorder (PTSD). We examined the relationship between PTSD symptoms and chronic pain in Croatian war veterans. Methods: A total of 156 war veterans with chronic pain were selected as the sample of this study. On the basis of medical records, interviews, and different self-report questionnaires (Mississippi Scale for Combat-Related PTSD, Impact of Event Scale, McGill Pain Questionnaire, Pain Outcomes Questionnaire-VA (POQ-VA), Brief Pain Inventory, Beck Depression Inventory, Quality of Life Questionnaire), the authors analyzed the interrelationships between chronic pain and chronic PTSD. Results: In our sample, 110 patients had severe symptoms of chronic PTSD. We found a statistically significant positive correlation between PTSD symptoms and pain intensity that influence everyday activities such as walking, personal hygiene, and independent dressing. There was significant correlation between PTSD symptoms and intensity of negative emotions, fear of possible injuries, and problems with concentration. We found a negative correlation between intensity of PTSD symptoms, vitality, energy level, and physical endurance. Veterans with PTSD compared to veterans without PTSD have a significantly higher level of pain and are less physically active, with a lower level of energy. However, there was no difference between veterans with PTSD and those without PTSD in evaluation of medical treatment. Conclusion: The relationship between chronic pain and chronic PTSD is very complex and requires a multidisciplinary approach in assessment and treatment.
ENG